2008
DOI: 10.1111/j.1462-2920.2007.01453.x
|View full text |Cite
|
Sign up to set email alerts
|

Manure‐amended soil characteristics affecting the survival of E. coli O157:H7 in 36 Dutch soils

Abstract: The recent increase in foodborne disease associated with the consumption of fresh vegetables stresses the importance of the development of intervention strategies that minimize the risk of preharvest contamination. To identify risk factors for Escherichia coli O157:H7 persistence in soil, we studied the survival of a Shiga-toxin-deficient mutant in a set of 36 Dutch arable manure-amended soils (organic/conventional, sand/loam) and measured an array of biotic and abiotic manure-amended soil characteristics. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
153
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(160 citation statements)
references
References 71 publications
6
153
1
Order By: Relevance
“…In an E. coli O157:H7 survival study in Dutch soils, the calculated detection time by the Weibull model was 54 to 105 days. Franz et al (2008) revealed that E. coli O157:H7 populations declined more rapidly under more oligotrophic soil conditions, which can be achieved by using manure with a relatively high carbon-to-nitrogen ratio and consequently, a relatively low rate of nutrient release. The pH and fiber content of manure used in soils also affected the survival of E. coli O157:H7 and Salmonella in soil (Franz et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In an E. coli O157:H7 survival study in Dutch soils, the calculated detection time by the Weibull model was 54 to 105 days. Franz et al (2008) revealed that E. coli O157:H7 populations declined more rapidly under more oligotrophic soil conditions, which can be achieved by using manure with a relatively high carbon-to-nitrogen ratio and consequently, a relatively low rate of nutrient release. The pH and fiber content of manure used in soils also affected the survival of E. coli O157:H7 and Salmonella in soil (Franz et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the easily available carbon content of the manure explained this decline rate (22). A study in organic manure-amended soil showed a faster pathogen decline when rates of nutrient flow were reduced (23). Moreover, it has been shown that E. coli can survive at higher densities and for longer periods in sawdust than in sand livestock beddings (24).…”
mentioning
confidence: 99%
“…Results from several studies have shown that various stresses influence the survival and growth of E. coli in soils, including: high and low temperature (11,21,25), limited moisture (1-3, 9, 21), variation in soil texture (25), organic matter content (1,5,11), solar radiation (30), and competition and predation (2,26). Topp et al (25) observed that E. coli was capable of growing in soils amended with autoclaved swine manure slurry.…”
mentioning
confidence: 99%